A SWOT–CSF Integrated Strategy Model for Strengthening Teachers’ Pedagogical Competence Through Professional Learning Communities in Primary Schools - Destisari Nurbani; Dedy Achmad Kurniady; Nani Hartini (JDMP (Jurnal Dinamika Manajemen Pendidikan), 2026)
Strengthening the quality of learning requires urgent improvements in teachers' pedagogical competence. Schools have developed Professional Learning Communities (PLCs) as collaborative learning forums to support continuous teacher development. However, limited studies have examined PLC implementation using a strategic management perspective. This study aims to formulate effective PLC implementation strategies to improve teachers' pedagogical competence at an Islamic Elementary School. A qualitative case study approach with a qualitative-dominant mixed-methods design was employed, using data collected through observation, interviews, and documentation, and supported by a SWOT analysis and Critical Success Factors (CSFs). The findings reveal key internal strengths, including strong teacher collaboration, an open organizational culture, and ICT support, as well as external opportunities derived from the Merdeka Curriculum policy and foundation support. The SWOT–CSF integration identified three priority strategies with the highest relevance scores: mentoring and knowledge transfer, open impact reporting, and ICT-based training material curation. This study contributes a data-driven strategic framework for PLC implementation, offering both theoretical and practical implications for strengthening teachers' pedagogical competence in primary school contexts.